The Contingency Theory of Managerial Accounting: A Comment. - Tiessen, Peter; Waterhouse, J.H. (The Accounting Review, 1978)
The article comments on the paper "The Contingency Theory of Managerial Accounting," by David C. Hayes. The intent and implications of Hayes's research were to provide a sufficiently rich description of organizational subunit performance so as to permit a delineation of the factors which cause certain costs to occur. Once the causal factors of cost have been determined, controllability can be more clearly defined and responsibility for the causal factors can be assigned to individuals within the organization who have control over them. The major contingencies associated with departmental effectiveness in Hayes's assessment model are: organizational subunit interdependence, subunit environmental relationships, and factors internal to the subunit of interest. In describing these model dimensions, Hayes states that the nature of departmental interdependence varies with organizational complexity and may be classified as either stable pooled, sequential, or reciprocal. Unfortunately, the nature of the contingency dimensions is ignored by Hayes in stating his propositions and in conducting and analyzing his empirical research.